PENGARUH HARGA, KUALITAS DAN IKLAN PRODUK TERHADAP MINAT BELI KEMBALI SKINCARE SCARLETT DI KALANGAN MAHASISWI JAKARTA - Dewi, Sita; Andhitiyara, Revan; Manoe, Wahi Silvana; Wennadi, Luky Yunia; Santoso, Hadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Skincare is one of the beauty products used for skin care. Skincare users are mostly women, because women want their skin to always be healthy and well-groomed. Skincare includes cosmetics where the growth of the cosmetics industry has increased. The ease of getting beauty products, especially skincare, relatively affordable prices, good and safe products, and the existence of vigorous promotions in mass media and social media make people all moved to buy skincare beauty products. People will be interested in repurchasing a product if they are satisfied with the product, either from the quality of the product, the price is considered affordable or the promotion is attractive. This study aims to determine the effect of price, product quality and product advertising on the interest in repurchasing Scarlett skincare among Jakarta female students, either partially or simultaneously. The population of this study were Jakarta students who used Scarlett skincare. The sample was 100 Jakarta female students, who were selected by accidental sampling. By using the logistic regression analysis method, the results showed that partially only product quality has a significant effect on the interest in repurchasing Scarlett skincare. While simultaneously, price, product quality, product advertising have a significant effect on the interest in repurchasing Scarlett skincare.